Qualitative Analysis of BPJS Employment Marketing Style in Medan City Towards Increasing Informal Membership in Medan City - Suci Anggreyni Br Sembiring Pelawi; Santri Handayani; Ignasia Edwina Sinaga; Siti Aisya; Mutiara Rizky Nasution; Veri Dandi Marbun; Thasya Angelina Lumban Tobing; Feni Anggraini; Wan Salwa Anindya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the marketing style of BPJS Ketenagakerjaan in the Medan City branch and its impact on increasing participation among informal workers. The method used is a qualitative approach with a case study design, allowing the researcher to explore in-depth the marketing strategies implemented, responses from informal workers, and the obstacles faced. The results show that although BPJS Ketenagakerjaan has implemented various marketing strategies such as digital media usage and direct socialization, the participation rate among informal workers remains low. Contributing factors include a lack of understanding of the program's benefits, perceptions of contribution costs as an additional burden, and limited access to information technology. This research recommends a more adaptive and educational marketing approach to enhance awareness and participation among informal workers.